PENGARUH TAKARAN MIKORIZA VESIKULA ARBUSKULA DAN PUPUK SP-36 TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (Zea mays saccharata L.) - Yudi Yusdian; Joko Santoso; Rafly Al Ghifari Ramadhan (Program Studi Agroteknologi Faperta UNIBBA, 2022)
Corn is still the second strategic commodity after rice because in some areas, corn is still the second staple food after rice. The purpose of this study was to obtain the best effect of the combination dosage of Mycorrhizal Vesicle Arabuscula (MVA) and SP 36 fertilizer on growth. and sweet corn (Zea mays saccharata Sturt.) of Talenta variety. The experiment was carried out in Pangkalan Village, Bumiwangi Village, Ciparay District, Bandung Regency, West Java Province. With an altitude of 702 meters above sea level, with a rainfall of 2,417.40 mm/year including the type of C3 rainfall according to Oldeman (1975). With a soil pH of 6.8. The experiment was carried out from April 2021 to June 2022. The research method used was an experimental method with a Randomized Block Design (RBD), which consisted of six treatments and was repeated four times, namely: A (10 g MVA and 0 g SP36), B (0 g MVA and 2.81 g SP36), C (5 g MVA and 1.41 g SP36) D (5 g MVA and 2.81 g SP36), E (10 g MVA and 1.41 g SP36) and F (10 g MVA and 2.81 g SP36). The number of plants in this experiment was 768 plants. The results showed that the combination dosage of 10 g MVA and 1.41 g SP36 (75 kg/ha) gave a better effect on: plant height, number of leaves, length of ear without stalks, and weight of cobs without husks per plot of sweet corn (Zea mays saccharata Sturt) Talenta variety. Keywords: corn, dosege, fertilizer, mocorrhiza, SP36